2022
DOI: 10.1158/0008-5472.can-21-1360
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of SWI/SNF with the Ribosome Regulates Translation and Confers Sensitivity to Translation Pathway Inhibitors in Cancers with Complex Perturbations

Abstract: Subunits from the chromatin remodelers mammalian SWItch/Sucrose Non-Fermentable (mSWI/SNF) are mutated, deleted or amplified in more than 40% of cancers. Understanding their functions in normal cells and the consequences of cancerous alterations will provide insight into developing new targeted therapies. Here we examined whether mSWI/SNF mutations increase cellular sensitivity to specific drugs. Taking advantage of the DepMap studies, we demonstrate that cancer cells harboring mutations of specific mSWI/SNF s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…We speculate that the effects of Brd9 KD on myoblast differentiation are due to dysregulation of ribosomal biogenesis and rRNA processing, as seven of the top ten GO terms identified from the pool of genes upregulated in Brd9 KD cells related to rRNA, ribosomes, and translation. mSWI/SNF proteins recently have been linked to altered translational efficiency in cancer cells via direct mechanisms and via inhibition of mSWI/SNF protein function by chemical inhibitors [65,66]; it is possible that altering the gene expression and the processing of ribosome components also promotes altered translational efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that the effects of Brd9 KD on myoblast differentiation are due to dysregulation of ribosomal biogenesis and rRNA processing, as seven of the top ten GO terms identified from the pool of genes upregulated in Brd9 KD cells related to rRNA, ribosomes, and translation. mSWI/SNF proteins recently have been linked to altered translational efficiency in cancer cells via direct mechanisms and via inhibition of mSWI/SNF protein function by chemical inhibitors [65,66]; it is possible that altering the gene expression and the processing of ribosome components also promotes altered translational efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…If most SWI/SNF functions have traditionally been linked to transcription regulation, recent reports [31][32][33][34] and our RIME results suggested that SWI/SNF defects might also alter RNA splicing or translation. We therefore hypothesized that some SWI/SNF-dependent signaling effects might occur uniquely at the protein level and investigated the effects of SWI/SNF subunit defects at both the transcriptome and proteome levels.…”
Section: Loss Of Individual Swi/snf Subunits Distinctly Alters Gene A...mentioning
confidence: 58%
“…Loss of ARID2 also led to decreased interactions of SMARCC2 with a subset of proteins involved in RNA metabolism or splicing (e.g. DDX24, log2FC = -2.06; SF3B1, log2FC = -3.08; p-adj < 0.05), or translation (e.g., RRP1B, log2FC = -4.51; NOP56, log2FC = -3.61; MYBBP1A, log2FC = -2.26; all p-adj < 0.001), reminiscent of the recently described role of SWI/SNF in alternative splicing in mammals 31,32 , endoplasmic reticulum homeostasis in yeast 33 , and dependency of SWI/SNF-altered cells on translation factors 34 .…”
Section: Loss Of Individual Swi/snf Subunits Variably Alters the Comp...mentioning
confidence: 84%
“…Cytoplasmic examples have been noted for SMARCA4 in corticotroph adenomas ( Animireddy et al 2021 ) and for ARID1B in pancreatic cancer ( Bilodeau et al 2006 ). Recent work has shown that mSWI/SNF subunits are detectible in the cytoplasm and associate with the ribosomal machinery ( Ulicna et al 2022 ). SMARCA4 and PBAF subunits were also found to influence translation through their association with the translational machinery.…”
Section: Remodelers and Their Mechanistic Link To Diseasementioning
confidence: 99%
“…SMARCA4 and PBAF subunits were also found to influence translation through their association with the translational machinery. The cytoplasmic SMARCA4 subunit in particular was shown to correlate with disease progression in primary tumors compared with local recurrences and metastatic breast cancer ( Ulicna et al 2022 ). Together, these results suggest new potential therapeutic targeting for the mSWI/SNF subunits identified in the cytoplasm ( Fig.…”
Section: Remodelers and Their Mechanistic Link To Diseasementioning
confidence: 99%